Diagnosis and management of a rare bilateral ovarian mixed germ cell tumor: a case report - Li, Xuanling; You, Min; Zhang, Xiaoyun; Wei, Jingjing; Lin, Guangyao; Tang, Qianjue; Xu, Lianwei (Frontiers in Oncology, 2025)
BackgroundMixed ovarian malignant germ cell tumors (MOGCTs) are rare neoplasms composed of two or more malignant germ cell components, representing less than 1% of all ovarian germ cell tumors. They primarily affect adolescents and young women, presenting a clinical challenge due to their histologic heterogeneity, potential for recurrence, and the need to balance oncologic safety with fertility preservation.Case presentationWe reported a 22-year-old woman diagnosed with a four-component MOGCT in the right ovary—comprising yolk sac tumor, immature teratoma, embryonal carcinoma, and dysgerminoma—along with a dysgerminoma component in the left ovary. Considering her age and fertility desire, fertility-sparing surgery was performed, followed by adjuvant BEP chemotherapy. At 12-month follow-up, the patient remained disease-free with regular menstruation and no signs of recurrence.ConclusionThis case highlights the feasibility of fertility-sparing treatment in patients with complex bilateral MOGCTs. Given the rarity and histological diversity of such tumors, individualized treatment planning, strict staging, and long-term surveillance are essential to optimize clinical outcomes and preserve reproductive potential.